PERAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERKEMBANGAN BMT UGT SIDOGIRI CABANG SURABAYA - Nuning Nurna Dewi; Achmad Fathoni Rodli; Maslahatus Saidah; Relita Rofiqoh; Maris Wahidatul ‘Ailah (Ecopreneur.12, 2022)
The research entitled "Transformational Leadership Role Towards the Development of BMT UGT Sidogiri Surabaya Branch" is the result of field research to answer the question: What is the transformational leadership style in BMT UGT Sidogiri Surabaya branch? What is the role of transformational leadership style towards the development of BMT UGT Sidogiri Surabaya branch?. Descriptive analysis of the analysis is describing and analyzing the data that the author obtained from observations, interviews, and documentation and conducting research at bmt UGT Sidogiri surabaya branch on the application of transformational leadership style and the role of transformational leadership style to developments in BMT UGT Sidogiri surabaya branch. The results showed that the leadership style of the head of BMT UGT Sidogiri surabaya branch has a transformational leader character according to Bass and Aviola (1994) known as "4 I", namely: (1). Idealized influence, (2). Inspirational motivation, (3). Intellectual stimulation, (4). Individualized consideration. Transformational leadership role has an impact on the development of BMT UGT Sidogiri, namely: (1). Improving Employee performance, (2). Improving employee professionalism, (3). Increasing employee creativity, (4). Increasing employee and customer confidence in BMT UGT Sidogiri Surabaya branch, (5). Improving the image of BMT UGT Sidogiri Surabaya branch